Rancang Ulang Strategi Keunggulan Bersaing Industri Retail Komponen Otomotif Dalam Upaya Meningkatkan Kinerja Perusahaan - Ruspeind; Supriyadi, Edy (SEKOLAH PASCASARJANA PRESS, 2017)
This research conducted to redesign competitiveness advantage strategy through differentiation, market orientation, innovation, and entrepreneur orientation which conduct at Retail Division, PT. Astra Otoparts,Tbk. Population in this study were customers who conduct transactions at Shop & Drive in area of Jakarta. 100 respondents used as samples in this study, while data collection used questionnaire with likert scale of 1 (disagree) to 5 (strongly agree). The method has been used Path Analysis to determine the inter-relationship between variables. In the other hand, determination of strategy is done by SWOT analysis. The result of data analysis showed the Chi-Square = 0:00, df = 0, P-value = 1.0000, RMSEA = 0.000 which research model proposed in this study can be accepted by the goodness of fit. Then from the causal analysis showed that differentiation, innovation and entrepreneurial orientation has connection to competitive advantage. In fact, the market orientation had no relationship with a competitive advantage. The relationship of causality was also shown between the competitive advantage with the performance of the company, with a significant impact. The result obtained that strategies which are best suited to implement such as: service development, new product variants, product warranty, and network expansion.